2021
DOI: 10.1007/s12519-021-00453-w
|View full text |Cite
|
Sign up to set email alerts
|

Role of ultrasound in the diagnosis of cervical tuberculous lymphadenitis in children

Abstract: Background To describe sonographic characteristics of cervical tuberculous lymphadenitis (CTBL) in children, clinical information, and sonograms of 348 lymph nodes (LNs) from 57 children with CTBL were retrospectively analyzed in this study. Methods We retrospectively reviewed the clinical data and sonograms of 348 LNs from 31 boys and 26 girls with CTBL, who were confirmed by pathology or laboratory examination, at the Hangzhou Red Cross Hospital between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Although some investigations gave a direction to this case namely USG, Mantoux test and radiograph while others were non-specific for making a final diagnosis. The USG imaging features considered in tubercular lymphadenitis include numbers, size, shape (determined by the short-to-long axis (S/L) ratio), echogenic hilus, edge, internal echogenicity, calcification, necrosis, matting of lymph node and adjacent soft tissue oedema [8]. Some of these pathognomonic feature were reported in the present case.…”
Section: Case Reportmentioning
confidence: 50%
“…Although some investigations gave a direction to this case namely USG, Mantoux test and radiograph while others were non-specific for making a final diagnosis. The USG imaging features considered in tubercular lymphadenitis include numbers, size, shape (determined by the short-to-long axis (S/L) ratio), echogenic hilus, edge, internal echogenicity, calcification, necrosis, matting of lymph node and adjacent soft tissue oedema [8]. Some of these pathognomonic feature were reported in the present case.…”
Section: Case Reportmentioning
confidence: 50%
“…However, there were many cases overlapping in the two scores between the two groups, and the value of elastic score in evaluating the response to treatment was limited. Strong echo in lymph nodes usually represents the transition of the lesion to the healing stage, and its size may increase with the disease course ( 15 ). This study showed no significant difference between the two groups, which may be related to the short treatment time of the included cases, and the correlation between this sign and prognosis could not be clearly determined at 1–2 months after treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The early manifestations of tuberculous lymphadenitis are swollen, tangled, firm, non-tender lymph nodes with a S/L (short diameter/long diameter) ratio greater than 0.5. In the late stage of the disease, the manifestations are caseous degeneration, necrosis, thin echoes, strong echoes, and suppuration in the lymph nodes, which on the US appear as multiple irregularly shaped, heterogeneous, hypoechoic masses with enhanced posterior echogenicity, calcifications, with a capsular or peripheral vascular distribution ( 18 ). Eventually, the inflammation in the lymph nodes spreads into the surrounding soft tissue, forming an abscess ( 18 ).…”
Section: Discussionmentioning
confidence: 99%